Getting to know the gradient f(x + h) f(x) x x+h Differentiation from first principles 400 360 320 P 280 f(x+h) 240 200 160 120 80 A f(x)40 0 0 0.5 x1 1.5 Gradient of AP = 2 2.5 f( x h) f( x) h 3 x3.5 +h 4 Differentiation from first principles 400 360 320 280 240 200 P f(x+h) 160 120 80 A f(x)40 0 0 0.5 x1 1.5 Gradient of AP = 2 2.5 f( x h) f( x) h x +3 h 3.5 4 Differentiation from first principles 400 360 320 280 240 200 160 P 120 f(x+h) 80 A f(x)40 0 0 0.5 x1 1.5 Gradient of AP = 2 2.5 x+ h f( x h) f( x) h 3 3.5 4 Differentiation from first principles 400 360 320 280 240 200 160 120 P 80 f(x+h) A f(x)40 0 0 0.5 x1 1.5 Gradient of AP = 2 x+ h 2.5 f( x h) f( x) h 3 3.5 4 Differentiation from first principles 400 360 320 280 240 200 160 120 80 f(x+h) f(x)40 A P 0 0 0.5 x1 x 1.5 +h Gradient of AP = 2 2.5 f( x h) f( x) h 3 3.5 4 Differentiation from first principles 400 360 320 280 240 200 160 120 80 A 40 f(x) 0 0 0.5 x1 1.5 2 Gradient of tangent at A = 2.5 3 Limit f( x h) f( x) h0 h 3.5 4 Finding the gradient using a secant line x+h Secant line y 2 y1 gradient x 2 x1 x 𝑦2 = 𝑓 𝑥 + ℎ = (𝑥 + ℎ)2 2 − 𝑥2 𝑥 + ℎ) 𝑓 ′ (𝑥) = 𝑥+ℎ −𝑥 𝑓 ′ (𝑥) 2ℎ𝑥 + ℎ2 = ℎ 𝑓 ′ (𝑥) = ℎ(2𝑥 + ℎ) ℎ Expand & simplify 𝑦1 = 𝑓 𝑥 = 𝑥 2 2 + 2ℎ𝑥 + ℎ2 ) − 𝑥 2 𝑥 𝑓 ′ (𝑥) = ℎ 𝑓 ′ 𝑥 = 2x + h This is the gradient of the Secant line As h → 𝟎 the secant line becomes the tangent x+h x 𝑓 ′ 𝑥 = lim 2x + h ℎ→0 𝑓 ′ 𝑥 = 2x So to find the gradient of 𝑓 𝑥 = 𝑥 2 for any value of x, we use the gradient function 𝑓 ′ 𝑥 = 2x Also known as the derivative of f In general The derivative of f(x) 𝑓 𝑥 + ℎ − 𝑓(𝑥) 𝑓 𝑥 = lim ℎ→0 ℎ ′ Hence find the derivative of 𝑓 𝑥 = 2𝑥 2 + 1 Differentiation from first principles f(x) = x3 ( x h)3 x 3 x 3 3 x 2 h 3 xh 2 h3 x 3 3 x 2 h 3 xh 2 h f( x h) f( x) h h h h (3 x 2 3 xh h 2 )h 3 x 2 3 xh h 2 h f '( x) Limit f( x h) f( x) 3x 2 h0 h 𝑓 𝑥 + ℎ − 𝑓(𝑥) 𝑓 𝑥 = lim ℎ→0 ℎ ′ 𝑓′ 𝑥 2 Differentiate: 𝑓 𝑥 = 2𝑥 + 1 2(𝑥 + ℎ)2 + 1 − (2𝑥 2 + 1) 𝑓 𝑥 = lim ℎ→0 ℎ 𝑓 𝑥 + ℎ − 𝑓(𝑥) = lim ℎ→0 ℎ ′ 𝑓′ 2(𝑥 2 + 2ℎ𝑥 + ℎ2 ) + 1 − (2𝑥 2 + 1) 𝑥 = lim ℎ→0 ℎ 2𝑥 2 + 4ℎ𝑥 + 2ℎ2 + 1 − 2𝑥 2 − 1 𝑓 𝑥 = lim ℎ→0 ℎ ′ 4ℎ𝑥 + 2ℎ2 𝑓 𝑥 = lim ℎ→0 ℎ ′ ℎ(4𝑥 + 2ℎ) ℎ→0 ℎ 𝑓 ′ 𝑥 = lim 𝑓 ′ 𝑥 = lim 4𝑥 + 2ℎ ℎ→0 𝑓 ′ 𝑥 = 4𝑥 Let’s find an easier general rule Here are some results – what’s the rule 𝑓 𝑥 = 3𝑥 2 + 2𝑥 𝑓 𝑥 = 5𝑥 3 − 7 𝑓′ 𝑥 = 6𝑥 + 2 𝑓′ 𝑥 = 15𝑥 2 𝑓 𝑥 = 𝑎𝑥 𝑛 + 𝐶, 𝑓 𝑥 = 𝑥 12 − 7𝑥 3 𝑓′ 𝑥 = 12𝑥 11 − 21𝑥 2 𝑓 ′ 𝑥 = 𝑎𝑛𝑥 𝑛−1 𝑓 𝑥 = 2𝑥 −4 𝑓′ 𝑥 = −8𝑥 −5 Differentiate the following … or find the derivative of f(x) 1. 𝑓 𝑥 = 𝑥 5 𝑓′ 𝑥 = 5𝑥 4 𝑥8 𝑓′ 𝑥 = 8𝑥 7 2. 𝑓 𝑥 = 3. 𝑓 𝑥 = 4. 𝑓 𝑥 = 5. 𝑓 𝑥 = 6. 𝑓 𝑥 = 1 𝑥4 3 𝑥 1 𝑥 5 𝑥3 𝑓 ′ 𝑥 4 =− 5 𝑥 𝑓′ 𝑥 = 𝑓′ 𝑥 1. 𝑓 𝑥 = 1 3 3 𝑥2 =− 1 2 𝑥3 3 5 5 𝑥2